2018
DOI: 10.1177/0743558418764089
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Positive Youth Development Through Teenagers-as-Teachers Programs

Abstract: A promising approach to support positive youth development is having adolescents serve as teachers for younger children. Through a qualitative interview study, we explored adolescents' development in their role serving as teachers for younger elementary-age children during out-of-school time; programs were managed by the University of California 4-H Youth Development Program. We interviewed 32 teenagers (median age 15; 27 female, 5 male) about their experiences, growth, and learning. Through consensus-based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
(45 reference statements)
1
18
0
1
Order By: Relevance
“…It has been found that teenagers can be effective teachers when provided adequate resources and support (Lee & Murdock, 2001). To ensure the success of the teenagers-as-teachers model, Lee and Murdock (2001) suggested that programs be designed including 10 essential elements:  dedicated adults who support teenagers, Cross-age teaching is not only beneficial for younger youth, but also provides educational, developmental, and emotional benefits for teenage teachers (Murdock et al, 2003;Shanahan, 2015;Weybright et al, 2016;Worker et al, 2018). In nutrition education programs specifically, use of teenage teachers can be just as effective as-or in some regards even more effective than-adult educators (Smith, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that teenagers can be effective teachers when provided adequate resources and support (Lee & Murdock, 2001). To ensure the success of the teenagers-as-teachers model, Lee and Murdock (2001) suggested that programs be designed including 10 essential elements:  dedicated adults who support teenagers, Cross-age teaching is not only beneficial for younger youth, but also provides educational, developmental, and emotional benefits for teenage teachers (Murdock et al, 2003;Shanahan, 2015;Weybright et al, 2016;Worker et al, 2018). In nutrition education programs specifically, use of teenage teachers can be just as effective as-or in some regards even more effective than-adult educators (Smith, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The HLA program brought health, science, teen leadership, and teamwork together to grow teens' self-efficacy in their own health, all the while putting them at the forefront of promoting healthy behaviors in members of their local community. The teens-as-teachers model is known for producing positive changes in the teen participants (Weybright et al, 2016;Worker et al, 2018).…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…The teens-as-teachers model has demonstrated promising results, with teens learning and adopting the healthful behavioral practices that they teach to youths . Further, the model provides opportunities for adolescents to extend learning for individual growth, and provides a nurturing space to contribute to community growth (Worker, Iaccopucci, Bird, & Horowitz, 2018). Collaborating with after-school tutoring and homework programs was a natural approach for 4-H, as many out-of-school programs lack capacity and resources to provide students with rigorous, project-based academic programming.…”
Section: Community Assessmentmentioning
confidence: 99%
“…Because of this, it is a view that empowers and values youth (Lerner et al 2005). In recent years, researchers have seen numerous positive results when implementing PYD strategies (Catalano et al, 2004;Ciocanel et al 2017;Larson 2000;Worker et al 2019). PYD's empowering message to youth along with these encouraging research findings make PYD a natural fit to be implemented into after-school programs.…”
Section: Methodsmentioning
confidence: 99%